ANALISIS STRUKTUR BATIN PUISI “DENGAN PUISI, AKU” KARYA TAUFIK ISMAIL - Susi Astriani; Yusep Ahmadi; Wika Nengsih (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Poetry is the most unique literary work because it is created from the poet's deepest contemplation, poetry is not just a work of art but an outpouring of a writer when he is happy, or when he is sad. Poetry is a very elegant way to convey the heart and express all the events that occur in everyday life to every human being. This poem has two structures, namely the physical structure and the inner structure. The author chose "With Poetry, Aku" by Taufik Ismail as the object of research, which means to know about the theme and the meaning contained in it. The formulation of the problem raised from this research is how the inner structure contained in the poem "With Poetry, Aku"?. This study aims to describe the inner structure of the theme, tone, feeling and message. By focusing on analyzing the inner structure of the researcher can perform analysis with clarity and facts. The method used in this study is a qualitative descriptive method. This poem has a result that contains the theme of humanity, has a charismatic tone, contains a sense of alienation due to the deteriorating conditions of the times, and has a mandate that everyone has a compassionate nature, continues to work, prays to god so that everything changes and life becomes better.